Effects of Goethite/Birnessite on Antimony Speciation in Yellow Soil from an Antimony Mining Area under Simulated Natural Conditions - Jingguang LIU; Ping ZHAO; Wei REN; Xue MA; Kaiying HE; Xiaping ZHU (Yankuang ceshi)
The antimony (Sb) mining area and its surrounding soil are severely polluted with antimony, and the degree of antimony pollution is closely related to its speciation in the soil. Iron and manganese oxides are the most active components of clay minerals in soil, affecting the transformation of antimony speciation in soil. Existing research focuses more on the effect of single iron and manganese oxides on the adsorption of exogenous antimony, while basic study on the effect of iron and manganese oxides on the transformation of antimony speciation in actual soil needs to be strengthened. This study described the in situ preparation of goethite (α-FeOOH) and birnessite (δ-MnO2) in soil, which were loaded onto antimony contaminated yellow soil (original soil) in the Qinglong antimony mining area, Guizhou Province to obtain Fe-loaded soil and Mn-loaded soil. Simulating the natural soil conditions, a 180-day flooding experiment of original soil, Fe-loaded soil and Mn-loaded soil was conducted. The transformation characteristics of soil antimony forms mediated by α-FeOOH and δ-MnO2 were explored. The results showed that flooding changed the redox characteristics of soil, affected the forms of iron and manganese oxides, and thus affected the distribution of antimony speciation. The loaded α-FeOOH mainly existed as amorphous iron, while the loaded δ-MnO2 existed in three forms: free manganese, amorphous manganese, and complex manganese. Compared with the original soil, the content of Sb in the suspension and weak acidic extracted antimony of Fe-loaded soil decreased by 88.3%−94.4% and 21.1%−65.9%, respectively; the content of reducible antimony and oxidizable antimony increased by 49.0%−67.2% and 74.3%−159%, respectively; Sb in the suspension, weak acidic extracted antimony, and reducible antimony in Mn-loaded soil increased by 14.2%−59.5%, 6.50%−32.6%, and 4.80%−23.3%, respectively, while oxidizable antimony decreased by 16.2%−58.5%. The various speciation of iron, manganese, and antimony in the original soil, Fe-loaded soil and Mn-loaded soil showed significant changes or a turning point in the trend after 30 days of flooding. Loading α-FeOOH promoted the transformation of weak acidic extracted antimony to reducible and oxidizable antimony in the soil, while loading δ-MnO2 promoted the transformation of oxidizable antimony to weak acidic extracted antimony and reducible antimony in the soil. This study provides a key scientific basis for the risk assessment and remediation technology of antimony contaminated soil. In the future, the control of soil antimony pollution needs to be combined with the regulation of iron and manganese oxide forms and the management of redox conditions to achieve long-term stabilization of antimony. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202502280032.